Language Testing as a Reflection Tool in Students’ Perspective: Insight for EFL Assessment - Citra Anggia Putri; Doli Rotua Sinaga; Meisuri Meisuri (JELITA, 2025)
This study uniquely explores language testing's dual role as an evaluative and reflective tool, offering actionable recommendations for improving teaching practices in EFL contexts. Integrating listening and speaking assessments highlights how reflective tools can enhance communicative skills and pedagogical strategies in higher education. The findings underline the need for innovative approaches to address students' speaking confidence and practical teaching implications. The method used in this study is a mixed approach, combining quantitative through a survey of 25 third-year students from the English literature department of Universitas Negeri Medan and qualitative through interviews and class observations. The results showed that most students felt that the listening and speaking tests helped identify their weaknesses, provide clear feedback, and increase their confidence. However, while this test is beneficial, there are challenges in increasing student confidence, especially in speaking. The implications of this study suggest that using tests as a reflection tool can improve the quality of communication skills teaching and learning, but further support is needed to achieve optimal results.